2022
DOI: 10.1108/jfbm-05-2022-0073
|View full text |Cite
|
Sign up to set email alerts
|

Exploring entrepreneurial qualities for the sustainability of family businesses in Pakistan

Abstract: PurposeThe purpose of this study to explore the qualities of the entrepreneur which are required for the sustainability of the family business. The sustainability rate of family business has remained low, particularly with the generation change in the long term. In addition, the body of knowledge on entrepreneurial qualities in relation to family business sustainability is fragmented. Hence, an in-depth understanding on this phenomenon is imperative.Design/methodology/approachThis study used qualitative study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Way power reveals the individual's belief that goals can be attained, that one can compose a plan to achieve one's goals (C.R. Snyder, 2000), and will power reveals a recognition of the ability to formulate pathways to attain those goals (Charles R. Snyder, 2002;Jamil et al, 2023). Morrow (2009) researched the relationship between hope and entrepreneurship and found that successful entrepreneurs exhibit higher hopes than others as it anticipates many benefits, such as enhanced social satisfaction and better health outcomes.…”
Section: Hopementioning
confidence: 99%
“…Way power reveals the individual's belief that goals can be attained, that one can compose a plan to achieve one's goals (C.R. Snyder, 2000), and will power reveals a recognition of the ability to formulate pathways to attain those goals (Charles R. Snyder, 2002;Jamil et al, 2023). Morrow (2009) researched the relationship between hope and entrepreneurship and found that successful entrepreneurs exhibit higher hopes than others as it anticipates many benefits, such as enhanced social satisfaction and better health outcomes.…”
Section: Hopementioning
confidence: 99%
“…The contribution of family businesses to the economy is significant in many countries, as reported by authors including (Miroshnychenko et al, 2021;Ratten, 2023;Schillaci et al, 2013). However, family business has only received limited coverage in the extant literature (King et al, 2022;Jamil et al, 2023;Lyons et al, 2023). Furthermore, the development of family business theories is limited, especially for describing the sustainability of the family business by using strategic entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…2 the evaluation of the responsible behavior of companies and the prediction of possible future financial results also based on non-financial information [5]. The activities carried out by companies in the field of ESG are not only intended to contribute to the mitigation of climate change by directing the European Union on the path of green transformation with the ultimate goal of achieving climate neutrality by 2050 but also to support the transformation to a fair and prosperous society with a modern and competitive economy [6]. The European Commission has approved the Corporate Sustainability Reporting Directive (CSRD), aimed at reporting sustainability information in the form of a sustainability report (ESG report).…”
Section: Introductionmentioning
confidence: 99%